Effect of cognitive insight on clinical insight from pre-morbid to early psychosis stages. (July 2022) - Xu, LiHua; Hao, Di; Wei, YanYan; Cui, HuiRu; Qian, ZhenYing; Wang, YingChan; Hu, Hao; Su, WenJun; Tang, XiaoChen; Hu, YeGang; Tang, YingYing; Zhang, TianHong; et al.
Highlights: Self-reflectiveness of cognitive insight decreased as the positive symptoms increased. Interventions to improve cognitive insight may be beneficial to maintain good clinical insight. Self-certainty of cognitive insight may have different implications when symptoms are mild and may prompt individuals to seek help. Abstract: Poor cognitive insight, including low self-reflectiveness and high self-certainty, contributes to poor clinical insight, which includes awareness of illness, relabelling of specific symptoms, and treatment compliance. However, inconsistent results regarding cognitive insight among individuals at clinical high risk of psychosis (CHR) have been reported. This study investigated the difference in cognitive insight among groups with different severity of positive symptoms and analysed the effect of cognitive insight on clinical insight in each group. All participants, including CHR individuals with 3 or 4 points (L-Pitem, n = 85) and 5 points (H-Pitem, n = 37) on any positive-symptom item of the Scale of Prodromal Syndromes, and patients with first-episode psychosis (FEP, n = 59), were measured cognitive and clinical insight using the Beck Cognitive Insight Scale and the Schedule of Assessment of Insight, respectively. The self-reflectiveness of cognitive insight was highest in the L-Pitem group and lowest in the FEP group. Self-reflectiveness was positively associated with awareness of illness in the L-Pitem and FEP groups; both self-reflectiveness and self-certainty was positively associated with treatment compliance in the L-Pitem group. Improving self-reflectiveness of cognitive insight may conduce to good clinical insight. Self-certainty may have different implication to individuals with mild prodromal symptoms.